Condition of Euphausia crystallorophias off East Antarctica in winter in comparison to other seasons - Nicol, S; Patti Virtue; King, R; Davenport, SR; McGaffin, AF; Nichols, P (2004)
Antarctic coastal krill (Euphausia crystallorophias) were collected in Austral winter (July/August) 1999 in the Mertz Glacier polynya off the coast of East Antarctica and were compared to krill collected off East Antarctica during summer in 1996 and 2001 and spring 1999. A range of experiments and measurements were conducted to assess their relative condition in winter and summer. Krill collected in winter had pale yellow-green digestive glands, indicating some recent feeding activity. The size of the digestive glands was small relative to those of krill caught in summer. This indicates that feeding had been occurring at low levels during the collection period. Growth rates, measured using the instantaneous growth rate methodology, were close to zero in winter (range -5% to 7% per moult). This was an indication that some food had been available during the period of the moult cycle. Growth rates in spring ranged from -0.5% to +8.7% per moult and from 4% to 12% per moult in the summer. The mean length of the winter moult cycle (68 days) was considerably greater than the measured intermoult period in summer and spring (24-33 days). Lipid levels were low in winter, less than 5% of body weight, compared to summer levels of âˆ¼15% (dry weight). Winter krill were richer in wax esters and poorer in polar lipids than specimens collected in summer. Krill in winter were lacking in C16 PUFA that are markers of the phytoplankton diet common in summer krill. Krill caught in the winter had significantly higher levels of 20:1 and 22:1 fatty acids (2.3%) and alcohols (8.1%) than krill sampled in summer (0.2%, 0%), indicating a shift to a carnivorous diet. Results from this study suggest that E. crystallorophias respond to low food abundance during the winter through metabolic and physiological processes. These processes were reflected in a decrease in growth rate and a significant increase in the intermoult period. The process of lipid utilisation and switching to a carnivorous/detrital type diet are also overwintering ...